Between Consecutive Fractures: Time and Sex as Dominant Factors in Type and Severity Concordance of Contralateral Hip Injuries - Neta Leshem; Ido Stahl; Farouk Khury; Ianiv Trior Simonovich (Biomedicines)
Background/Objectives: Hip fractures present a global public health concern, with a forecasted rise in incidence and having associated increased mortality rates. This study aimed to investigate whether the AO Foundation/Orthopaedic Trauma Association (AO/OTA) classification of a first hip fracture can predict the location and severity of a subsequent contralateral fracture. Methods: We retrospectively evaluated patients with non-simultaneous bilateral hip fractures between January 2000 and February 2021 and analyzed the type and severity of each fracture using the AO/OTA classification system, interval between fractures (TI), and patients’ characteristics, including sex, age at time of each fracture, and radiographic measurements of hip morphology. Results: The study included 182 fractures in 91 patients (68% women, mean age: 79.5 and 82.2 years at first and second fractures, respectively; mean TI: 975 days). A strong association (lambda = 0.437, p < 0.001) was demonstrated between the first and second fracture classifications, which was higher in men (lambda = 0.60, p < 0.001) and for TI < 3 years (lambda = 0.625–0.688, p < 0.001). The mean TI was significantly shorter between the first and subsequent identical fractures than between different fracture types. However, mean hip morphological features did not significantly differ between groups. Conclusions: The initial hip fracture classification significantly predicted the type and severity of a subsequent contralateral fracture, particularly within 3 years and in men. Providing appropriate patient guidance and preventive measures is crucial, particularly for those with primary fractures that are associated with higher morbidity and mortality. Specific fracture-focused interventions, such as preventive intramedullary nail fixation, should be considered.